An international report on bacterial communities in esophageal squamous cell carcinoma. Issue 11 (11th August 2022) - Nomburg, Jason; Bullman, Susan; Nasrollahzadeh, Dariush; Collisson, Eric A.; Abedi‐Ardekani, Behnoush; Akoko, Larry O.; Atkins, Joshua R.; Buckle, Geoffrey C.; Gopal, Satish; Hu, Nan; Kaimila, Bongani; Khoshnia, Masoud; et al.
Abstract: The incidence of esophageal squamous cell carcinoma (ESCC) is disproportionately high in the eastern corridor of Africa and parts of Asia. Emerging research has identified a potential association between poor oral health and ESCC. One possible link between poor oral health and ESCC involves the alteration of the microbiome. We performed an integrated analysis of four independent sequencing efforts of ESCC tumors from patients from high‐ and low‐incidence regions of the world. Using whole genome sequencing (WGS) and RNA sequencing (RNAseq) of ESCC tumors from 61 patients in Tanzania, we identified a community of bacteria, including members of the genera Fusobacterium, Selenomonas, Prevotella, Streptococcus, Porphyromonas, Veillonella and Campylobacter, present at high abundance in ESCC tumors. We then characterized the microbiome of 238 ESCC tumor specimens collected in two additional independent sequencing efforts consisting of patients from other high‐ESCC incidence regions (Tanzania, Malawi, Kenya, Iran, China). This analysis revealed similar ESCC‐associated bacterial communities in these cancers. Because these genera are traditionally considered members of the oral microbiota, we next explored whether there was a relationship between the synchronous saliva and tumor microbiomes of ESCC patients in Tanzania. Comparative analyses revealed that paired saliva and tumor microbiomes were significantly similar with a specific enrichment of Fusobacterium and Prevotella in the tumor microbiome. Together, these data indicate that cancer‐associated oral bacteria are associated with ESCC tumors at the time of diagnosis and support a model in which oral bacteria are present in high abundance in both saliva and tumors of some ESCC patients. Abstract : What's new? Striking geographic patterns in the global incidence of esophageal squamous cell carcinoma (ESCC), reflected most notably in disproportionately high incidence rates in parts of Africa and Asia, remain unexplained. A factor suspected of driving these patterns is the microbiome. Here, analysis of bacterial communities in ESCC tumors from nine countries across different regions of the world shows that bacteria linked to other gastrointestinal cancers are associated with ESCC. Moreover, composition of the saliva microbiome was correlated with composition of the ESCC tumor microbiome. Further research is needed to better understand the role of the oral microbiome in ESCC pathogenesis.